Paving the Path : Lessons from Chile’s Experiences as a Sovereign Issuer for Sustainable Finance Action - Boitreaud, Sebastien (World Bank, Washington, DC, 2021)
Climate risks are on the rise globally. For emerging market countries such as Chile, these risks can manifest as an increased propensity for drought, wildfires, flood events, and landslides. As a result, governments are increasingly prioritizing policy solutions that will support an economic transition to mitigate the impact of climate change while also supporting households and communities as they adapt to the changing risk landscape. The financial sector is playing a key role in supporting a just economic transition. For many emerging market countries, the sovereign is the largest issuer of domestic debt, and the instruments and issuance path they choose can be key toward influencing downstream financial sector activity. For their part, global investors are becoming more attuned to the environmental, social, and governance (ESG) factors that underpin sovereign debt instruments. This report explores Chile’s sovereign issuer options, opportunities, and challenges through the lens of its recent decisions to issue green, social, and sustainable debt instruments.